2015
DOI: 10.3390/ijms160612405
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Stress and Antioxidative Mechanisms in Arabidopsis thaliana after Uranium Exposure at pH 7.5

Abstract: To evaluate the environmental impact of uranium (U) contamination, it is important to investigate the effects of U at ecologically relevant conditions. Since U speciation, and hence its toxicity, strongly depends on environmental pH, the present study aimed to investigate dose-dependent effects of U at pH 7.5. Arabidopsis thaliana plants (Mouse-ear Cress) were exposed for three days to different U concentrations at pH 7.5. In the roots, the increased capacities of ascorbate peroxidase and glutathione reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[7][8][9][10][11] Uranium inhibits plant growth, modifies root growth and architecture, disrupts mineral nutrition and homeostasis, and affects photosynthesis. [12][13][14][15][16][17][18][19] At the cellular level, U induces nitric oxide and hydrogen peroxide production and triggers defence mechanisms against oxidative stress. 19,20 Also, U perturbs iron, phosphate and manganese homeostasis 9,14,21,22 and triggers important changes in the metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Uranium inhibits plant growth, modifies root growth and architecture, disrupts mineral nutrition and homeostasis, and affects photosynthesis. [12][13][14][15][16][17][18][19] At the cellular level, U induces nitric oxide and hydrogen peroxide production and triggers defence mechanisms against oxidative stress. 19,20 Also, U perturbs iron, phosphate and manganese homeostasis 9,14,21,22 and triggers important changes in the metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…iron, calcium, phosphorus, magnesium), and hormone synthesis and distribution ( i.e. auxin, jasmonic acid and salicylic acid) (Vanhoudt et al, 2010; Vanhoudt et al, 2011; Doustaly et al, 2014; Saenen et al, 2014; Saenen et al, 2015; Serre et al, 2019; Wu et al, 2022; Chen et al, 2022; Chen et al, 2023). In addition, U exposure leads to an overproduction of reactive oxygen species (ROS) (Gupta et al, 2020; Wu et al, 2022; Xiao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Uranium interferes with plant nutrition, photosynthesis, and induces an oxidative stress (e.g. Vanhoudt et al, 2011aVanhoudt et al, ,b,c, 2014Aranjuelo et al, 2014;Saenen et al, 2014Saenen et al, , 2015Tewari et al, 2015). Also, it has been shown that U perturbs iron and phosphate homeostasis and may lead to phosphate starvation (Misson et al, 2009;Doustaly et al, 2014;Berthet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%